2008
DOI: 10.1152/ajpendo.90260.2008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of very-low-density lipoprotein and chylomicrons by streptozotocin-induced diabetic rat heart: effects of diabetes and lipoprotein preference

Abstract: Niu YG, Evans RD. Metabolism of very-low-density lipoprotein and chylomicrons by streptozotocin-induced diabetic rat heart: effects of diabetes and lipoprotein preference. Am J Physiol Endocrinol Metab 295: E1106 -E1116, 2008. First published September 9, 2008 doi:10.1152/ajpendo.90260.2008.-Very-low-density lipoprotein (VLDL) and chylomicrons (CM) are major sources of fatty acid supply to the heart, but little is known about their metabolism in diabetic myocardium. To investigate this, working hearts isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 67 publications
3
15
1
Order By: Relevance
“…By comparison, NEFA oxidation in these experiments was about 3-fold higher than CM-TAG oxidation by control hearts (and hence comparable to CM-TAG oxidation by diabetic hearts) [27] suggesting a general dysregulation of fatty acid beta-oxidation in the absence of glucose uptake. STZ-diabetic rat hearts utilised rat CM-TAG to a greater extent (about 50% more) than control rat hearts, consistent with increased cardiac LPL activity [22], whilst STZ-diabetic rat CMs were utilised even more avidly by both diabetic and non-diabetic rat hearts (about doubled), suggesting functional/composition differences in STZ-CM [22]. Similar studies with type 2 diabetic Zucker (ZDF) rats found comparable results: diabetic hearts utilised diabetic CM to a greater extent than controls, due principally to increased TAG-FA oxidation rather than esterification of TAG-derived FA into cellular lipids [23], and was associated with increased LPL activity in diabetic hearts [23].…”
Section: Accepted Manuscriptmentioning
confidence: 57%
See 4 more Smart Citations
“…By comparison, NEFA oxidation in these experiments was about 3-fold higher than CM-TAG oxidation by control hearts (and hence comparable to CM-TAG oxidation by diabetic hearts) [27] suggesting a general dysregulation of fatty acid beta-oxidation in the absence of glucose uptake. STZ-diabetic rat hearts utilised rat CM-TAG to a greater extent (about 50% more) than control rat hearts, consistent with increased cardiac LPL activity [22], whilst STZ-diabetic rat CMs were utilised even more avidly by both diabetic and non-diabetic rat hearts (about doubled), suggesting functional/composition differences in STZ-CM [22]. Similar studies with type 2 diabetic Zucker (ZDF) rats found comparable results: diabetic hearts utilised diabetic CM to a greater extent than controls, due principally to increased TAG-FA oxidation rather than esterification of TAG-derived FA into cellular lipids [23], and was associated with increased LPL activity in diabetic hearts [23].…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…Of the VLDL-TAG-FA assimilated, about one quarter was incorporated into tissue lipids whilst the remainder was oxidised; by contrast, about 90% of CM-TAG was oxidised; the metabolic partitioning was not affected by NEFA [16]. Comparable results have also been reported [15,22,23]. However, other authors demonstrate competition between NEFA and VLDL-TAG.…”
Section: Cardiac Vldl-tag Utilisationmentioning
confidence: 58%
See 3 more Smart Citations